The Contribution of Students Schemata Toward Students Reading Comprehension Achievement at Fourth Semester of Lakidende University Learners - Fadli, M.; Wahyudi, Iin; ., Sukmawati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
The contribution of Schemata toward Reading Comprehension: A Case of their contribution at fourth semester of Lakidende University learners. Schemata have an important role in the process of reading. With regard to reading in a foreign language, one crucial determinant of reading comprehension is the amount of background knowledge readers have. Although readers can turn printed symbols into sounds and word accurately, it cannot guarantee their comprehension. Inadequate background knowledge especially cultural one can have an effect on reading comprehension.The objective of this study are to find out the contribution of students schemata toward students reading comprehension achievement at fourth semester of Lakidende University learners. The population of this research are all the fourth semester of lakidende university learners who enrolled in academic year 2020/2021 with 17 students.  The data will collect through questionnaire and tests. After collecting the data, the data will analyze by statistically. The first step in analyzing data are checked the normality, homogeneity and linearity of the data as requirement to apply the inferential statistic on non inferential statistic parameters. In testing the hypothesis, T-Test analysis will apply by using SPSS 16 version